Navigating Human, Organizational, and Societal Transformation in an Era of Uncertainty and Innovation: Reflections on the Current Issue - Giri, Bishnu (Journal of Emerging Management Studies, 2026)
The contemporary world is witnessing profound transformations driven by technological advancement, changing workforce expectations, evolving financial realities, and increasing demands for social responsibility and institutional effectiveness. These shifts have created new challenges and opportunities for individuals, organizations, policymakers, and communities. The articles featured in this issue collectively explore these emerging dynamics through diverse yet interconnected perspectives spanning retirement planning, entrepreneurship education, employee well-being, corporate social responsibility, financial behavior, digital leadership, investment decision-making, and youth migration. Together, they demonstrate how human attitudes, competencies, institutional environments, and socio-economic structures influence decision-making and developmental outcomes. While some studies focus on individual-level factors such as financial literacy, emotional intelligence, self-efficacy, and risk tolerance, others examine organizational and societal dimensions including living wages, corporate citizenship, educational ecosystems, technological transformation, and brain drain. By bringing these perspectives together, this issue contributes to a deeper understanding of how individuals and institutions navigate complexity, uncertainty, and change in pursuit of sustainable development and inclusive progress. The collection offers valuable insights for academics, practitioners, business leaders, educators, and policymakers seeking evidence-based approaches to address contemporary challenges in both local and global contexts.